Reference values for the 1-minute sit-to-stand test to assess functional capacity and short-term mortality in people with idiopathic pulmonary fibrosis and fibrotic connective tissue related interstitial lung diseases: a prospective real-world cohort study - Meng-Yun Tsai; Kuo-Tung Huang; Chiann-Yi Hsu; Yi-Hsuan Yu; Pin-Kuei Fu (BMC Pulmonary Medicine)
Abstract Background Early identification of functional decline in fibrotic interstitial lung disease (F-ILD) is crucial for timely treatment and improved survival. While the 6-minute walk test (6MWT) is the standard for functional evaluation, it has practical limitations. The 1-minute sit-to-stand test (1MSTS) offers a simpler alternative; however, its correlation with the 6MWT in F-ILD patients remains unclear. This study aims to establish reference values for the 1MSTS in assessing functional capacity, evaluate its correlation with the 6MWT, and explore its utility in predicting 18-month mortality in F-ILD patients. Methods This prospective study enrolled participants diagnosed with F-ILD based on multidisciplinary team discussions. Assessments included the 1MSTS, 6MWT, pulmonary function test (PFT), GAP score, mMRC scale, and Charlson Comorbidity Index (CCI). The association between 1MSTS repetitions and other variables was calculated using Spearman’s rho. Bland-Altman plots assessed the agreement between 1MSTS repetitions and the 6MWT. Predictors of 18-month mortality were evaluated using ROC curve and Kaplan-Meier curve. Results Of the 150 F-ILD patients, 37 (24.6%) had idiopathic pulmonary fibrosis (IPF), and 113 (75.4%) had connective tissue disease-related ILD (CTD-ILD). Using ≤ 23 repetitions as the cutoff for functional impairment in 1MSTS, 74 (47.3%) patients were classified as impaired. The 1MSTS significantly predicted 18-month mortality and demonstrated moderate correlations with GAP score (rs = -0.49), mMRC scale (rs = -0.47), and 6MWT distance (rs = 0.65). Bland-Altman analysis indicated agreement between 1MSTS repetitions and 6MWT distance. Using ≤ 23 repetitions as the cutoff value for the 1MSTS to predict 18-month mortality, the mortality rate was 76.4%, with an AUC of 0.81. Conclusions The findings suggest that ≤ 23 repetitions in the 1MSTS can serve as an indicator of functional impairment, demonstrate a good correlation with 6MWT distance, and effectively predict 18-month mortality in patients with F-ILD. Clinical trial number Not applicable.